ORGANIZATIONAL CULTURE AND TOP MANAGEMENT SUPPORT: HOW TO INFLUENCE THE INTERNAL CONTROL OF ACCOUNTING INFORMATION SYSTEMS - Asep Effendi (INFOKUM, 2019)
compete in order to maintain the survival of the company. Technological progress is experiencing very rapid development in all fields to improve company performance in various sectors. Technology. Accounting information system is the most important part needed by companies related to financial data. To produce quality information, a quality accounting information system is needed. The purpose of this study is to determine how much influence organizational culture, top management support, and internal control have on the quality of accounting information systems at PT PLN (Persero) ULP Bandung. The method used in this research is descriptive and verification method with a quantitative approach. The sample in this study were 30 respondents from the finance and accounting information system at PT PLN (Persero) ULP Bandung. The analytical method used is multiple linear regression analysis and to partially test the hypothesis used t-test. The results of this study indicate that: 1) Organizational Culture has a significant effect on the Quality of Accounting Information Systems, 2) Top Management Support has a significant effect on the Quality of Accounting Information Systems, 3) Internal Controls have a significant effect on the Quality of Accounting Information Systems at PT PLN (Persero) ULP Bandung